Cerebral effects of glucagon‐like peptide‐1 receptor blockade before and after Roux‐en‐Y gastric bypass surgery in obese women: A proof‐of‐concept resting‐state functional MRI study. Issue 2 (5th November 2020) - van Duinkerken, Eelco; Bernardes, Gabriel; van Bloemendaal, Liselotte; Veltman, Dick J.; Barkhof, Frederik; Mograbi, Daniel C.; Gerdes, Victor E. A.; Deacon, Carolyn F.; Holst, Jens J.; Drent, Madeleine L.; Diamant, Michaela; ten Kulve, Jennifer; et al.
Abstract: Aim: To assess the effects of Roux‐en‐Y gastric bypass surgery (RYGB)‐related changes in glucagon‐like peptide‐1 (GLP‐1) on cerebral resting‐state functioning in obese women. Materials and Methods: In nine obese females aged 40‐54 years in the fasted state, we studied the effects of RYGB and GLP‐1 on five a priori selected networks implicated in food‐ and reward‐related processes as well as environment monitoring (default mode, right frontoparietal, basal ganglia, insula/anterior cingulate and anterior cingulate/orbitofrontal networks). Results: Before surgery, GLP‐1 receptor blockade (using exendin9‐39) was associated with increased right caudate nucleus (basal ganglia network) and decreased right middle frontal (right frontoparietal network) connectivity compared with placebo. RYGB resulted in decreased right orbitofrontal (insula/anterior cingulate network) connectivity. In the default mode network, after surgery, GLP‐1 receptor blockade had a larger effect on connectivity in this region than GLP‐1 receptor blockade before RYGB (all P FWE  < .05). Results remained similar after correction for changes in body weight. Default mode and right frontoparietal network connectivity changes were related to changes in body mass index and food scores after RYGB. Conclusions: These findings suggest GLP‐1 involvement in resting‐state networks related to food and reward processes and monitoring of the internal and external environment, pointing to a potential role for GLP‐1–induced changes in resting‐state connectivity in RYGB‐mediated weight loss and appetite control.